2011
DOI: 10.1038/icb.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of highly variable 185/333 immune response proteins in the coelomocytes of the sea urchin, Heliocidaris erythrogramma

Abstract: The 185/333 proteins of sea urchins represent a family of highly variable immune response molecules with unknown functions. In this study, we show that 185/333 proteins are expressed by three cell types: amoebocytes, colourless spherule cells and gut-associated amoebocytes. A sub-population of amoebocytes express 185/333 proteins on the membranes of vesicles emanating from the trans-Golgi and which later fuse with the plasma membranes of the cells. The previously uncharacterized gut-associated amoebocytes also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…16 This is the same location as reported here for Sp185/333 + cells in S. purpuratus, which are also associated with the coelomic epithelium that covers the outer surface of the intestine. However, Sp185/333 + cells present in the columnar epithelium of the intestine in S. purpuratus were not reported in H. erythrogramma.…”
Section: Sp185/333 In the Intestinesupporting
confidence: 58%
See 2 more Smart Citations
“…16 This is the same location as reported here for Sp185/333 + cells in S. purpuratus, which are also associated with the coelomic epithelium that covers the outer surface of the intestine. However, Sp185/333 + cells present in the columnar epithelium of the intestine in S. purpuratus were not reported in H. erythrogramma.…”
Section: Sp185/333 In the Intestinesupporting
confidence: 58%
“…However, Sp185/333 + cells present in the columnar epithelium of the intestine in S. purpuratus were not reported in H. erythrogramma. 16 The intestinal localization of the Sp185/333 + cells within the columnar epithelium is strikingly similar to the variable region-containing chitin-binding proteins (VCBPs) expressed in intestine-associated cells in amphioxus, Branchiostoma floridae, and in the solitary tunicate, Ciona intestinalis. 29,30 It is noteworthy that both the Sp185/333 and the VCBP gene families have been described as highly diverse, 12,13,[29][30][31][32][33][34][35] that the VCBPs bind to bacteria and augment phagocytosis by hemocytes in C. intestinalis cells in the columnar epithelium of the intestine may be intestine cells, while the cells associated with the coelomic epithelium surrounding the intestine in contact with the coelomic fluid may be coelomocytes.…”
Section: Sp185/333 In the Intestinementioning
confidence: 94%
See 1 more Smart Citation
“…Of the expressed sequence tags from those screens, 73% matched to two previously uncharacterized sequences, DD185 (11) and EST333 (13). In S. purpuratus the gene family is called Sp185/333 because it has been reported in another echinoid species (14).…”
mentioning
confidence: 99%
“…The functional significance of this is unclear at present, although it has been suggested that they may form bridges between immune cells (Brockton et al, 2008). They do not appear to bind bacteria in the coelomic fluid but an immunostaining study has suggested that gut amoebocytes phagocytose 185/333-covered bacteria (Dheilly et al, 2011). Conclusive evidence for the exact role of these proteins in sea urchin immunity is eagerly awaited.…”
Section: A Varied Immune Response: Variable Lymphocyte Receptors In Jmentioning
confidence: 99%